Dental Students’ Preferences in Selecting Artificial Teeth for Older Adults' Dentures - Sapie, Muhammad Afif; Mohamad Hilmi, Nur Hanim Farhana; Rajali, Aiemeeza; Nik Zulkifeli, Nik Rahayyu; Mustafa, Nor Wati Nur Atikah; Dakhilallah Al Tarawneh, Hazem Mofreh (UI Scholars Hub, 2025)
Objective: Selecting and arranging acrylic resin teeth for dentures is essential to achieve a natural appearance; however, limited understanding and older adults’ aesthetic expectations may result in inconsistencies and increased patient visits. This study aimed to explore the methods and factors dental students prefer when selecting artificial teeth for dentures for older adults. Method: A validated questionnaire, including consent, demographics, and six domains of the methods with related factors for selecting acrylic teeth, was distributed to dental students of the Universiti Teknologi MARA (UiTM). The participants responded using a five-point Likert scale and closed-ended questions. Result: 161 dental students participated in the study (115 females, 71.4% and 46 males, 28.6%), divided into no-experience (n = 80, 49.7%) and experienced (n = 81, 50.3%) in treating older denture patients. Both groups preferred the visual shade selection method, with no-experience students' mean score is 3.88 ± 1.03 and experienced students' score is 4.11 ± 0.77 (p > 0.05). The digital shade selection method was the least preferred by no-experience students (2.98 ± 1.28) and experienced students (2.51 ± 1.33) (p < 0.05). The factors most influencing the selection were experience, light source, and characteristics of the tooth. Conclusions: Dental students preferred the visual shade selection method for choosing acrylic teeth in denture fabrication for older adults and were influenced by experience, light source, and natural tooth characteristics.